A synopsis of Digitaria (Paniceae, Panicoideae, Poaceae) in Mexico, including the new species Digitaria michoacanensis - Sánchez-Ken, J. Gabriel (Instituto de Ecología, A.C., 2022)
A new species, Digitaria michoacanensis from northern Michoacán and the adjacent part of the state of México in the central-west region of Mexico, is described. Pending an updated phylogenetic infrageneric classification of the genus; the new species is placed in the group Ternata with spikelets in groups of three or more. A synopsis with a key to the Mexican species of the genus Digitaria is also provided.